Pessimism preserved: real wages in the British Industrial Revolution - Allen, R; Allen, R (University of Oxford, 2007)
The paper compares Feinstein's and Clark's consumer price and real wage indices for the British industrial revolution. The sources for their weights and component price series are evaluated. While some of Clark's innovations are improvements, many of his changes degrade the price index. A new price index is developed using the best components of Clark's and Feinstein's. This index is much closer to Feinstein's than to Clark's. The implied growth in real wages is also close to Feinstein's and contradicts Clark's 'optimistic' view of rising working class living standards during the industrial revolution.